2019
DOI: 10.1149/2.0851910jes
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Assisted Regeneration of a Polymer Electrolyte Water Electrolyzer Contaminated with Metal Ion Impurities

Abstract: Polymer electrolyte water electrolysis (PEWE) is perceived as a key technology for conversion of renewable electricity in large-scale energy storage applications and deep decarbonization of the traditionally carbon-intensive mobility and chemical industry sectors. Since the price of hydrogen produced by PEWE is dominated by the price of electricity, it is crucial to ensure low degradation rates during the lifetime of a PEWE stack. This study aims to shed light onto the effects of cationic impurities that are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…Recovery of the voltage is immediately observed as the contaminant cations are moving to positions near the cathode catalyst layer where the impact of their presence is less severe. 36 When the electrochemical conditions reached steady state (∼30 min from switch to the fresh feed loop) all transient experiments were carried out, which took approximately 8 h. The last step of the experiment included operando regeneration of the electrolyzer by introducing dilute H 2 SO 4 acid (0.5 mmol l −1 ) to the cathode cell compartment. Initially, a drop of the performance can be seen due to a temperature effect after the acid (which was at room temperature) was injected.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recovery of the voltage is immediately observed as the contaminant cations are moving to positions near the cathode catalyst layer where the impact of their presence is less severe. 36 When the electrochemical conditions reached steady state (∼30 min from switch to the fresh feed loop) all transient experiments were carried out, which took approximately 8 h. The last step of the experiment included operando regeneration of the electrolyzer by introducing dilute H 2 SO 4 acid (0.5 mmol l −1 ) to the cathode cell compartment. Initially, a drop of the performance can be seen due to a temperature effect after the acid (which was at room temperature) was injected.…”
Section: Resultsmentioning
confidence: 99%
“…IV curve simulation and HFR hysteresis.-In our previous publication, which focused mostly on the impact of contaminants on electrochemical performance, 36 it has been shown that for contaminated membranes a very distinct hysteresis in the HFR appears when measuring Current-Voltage (IV) curves with ascending and descending current densities in cycles. Using the model that has been validated with experimental data, we inserted new transport parameters that match Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations